Effects of prenatal exercise on incidence of congenital anomalies and hyperthermia: a systematic review and meta-analysis. Issue 2 (18th October 2018) - Davenport, Margie H; Yoo, Courtney; Mottola, Michelle F; Poitras, Veronica J; Jaramillo Garcia, Alejandra; Gray, Casey E; Barrowman, Nick; Davies, Gregory A; Kathol, Amariah; Skow, Rachel J; Meah, Victoria L; Riske, Laurel; et al.
Abstract : Objective: To investigate the relationships between exercise and incidence of congenital anomalies and hyperthermia. Design: Systematic review with random-effects meta-analysis . Data sources: Online databases were searched from inception up to 6 January 2017. Study eligibility criteria: Studies of all designs were eligible (except case studies and reviews) if they were published in English, Spanish or French, and contained information on population (pregnant women without contraindication to exercise), intervention (subjective or objective measures of frequency, intensity, duration, volume or type of exercise, alone ["exercise-only"] or in combination with other intervention components [e.g., dietary; "exercise + co-intervention"]), comparator (no exercise or different frequency, intensity, duration, volume or type of exercise) and outcome (maternal temperature and fetal anomalies). Results: This systematic review and meta-analysis included 'very low' quality evidence from 14 studies (n=78 735) reporting on prenatal exercise and the odds of congenital anomalies, and 'very low' to 'low' quality evidence from 15 studies (n=447) reporting on maternal temperature response to prenatal exercise. Prenatal exercise did not increase the odds of congenital anomalies (OR 1.23, 95% CI 0.77 to 1.95, I 2 =0%). A small but significant increase in maternal temperature was observed from pre-exercise to both during and immediately after exercise (during: 0.26°C, 95% CI 0.12 to 0.40, I 2 =70%; following: 0.24°C, 95% CI 0.17 to 0.31, I 2 =47%). Summary/Conclusions: These data suggest that moderate-to-vigorous prenatal exercise does not induce hyperthermia or increase the odds of congenital anomalies. However, exercise responses were investigated in most studies after 12 weeks' gestation when the risk of de novo congenital anomalies is negligible.